Analysis of Employee Competency Development at the Corporate Headquarters of Makassar Raya Makassar City Market - Jumalia Mannayong; Haerul Haerul (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
In assessing the success of an agency, it can be seen from the human resources that drive the agency itself. The purpose of this study was to determine the development of employee competencies. This study uses descriptive qualitative methods using data collection methods, namely interviews, document review, and observation. The data collection instruments used were interview guidelines, document review guidelines, and observation guidelines as well as data analysis techniques by reducing data presentation, drawing conclusions, and verification. After that test the validity of the data with triangulation techniques. The results of this study indicate that overall employee competency development is in the good category. Regarding employee competency development at the Makassar Raya Regional Makassar Regional Office Corporate Office, reviewed from the Motif, Character, Self-Concept, Knowledge, and Skills aspects, but there are still some indicators that need to be improved to maximize the development of employee competence at the Regional Makassar Regional Office. Makassar Raya.